Analisis Tata Kelola Teknologi Informasi Untuk Meningkatkan Mutu Sumber Daya Manusia Menggunakan Framework COBIT 5 (Studi Kasus: Politeknik Pariwisata Negeri Lombok) - Gigih Mathori Basil; Nadiyasari Agitha; Moh. Ali Albar (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
Information technology governance is an integrated part of the organization's management that governs leadership, the organization's organizational structure of the processes that govern information technology is used optimally. Human resources are currently not managed properly, which has not met the needs of IT human resources in Central Lombok. To solve this problem, the writer implements IT Governance using the COBIT 5 framework in the Lombok State Polytechnic. This study will provide recommendations for the improvement of IT problems in the Poltekpar Negeri Lombok and can be used as a reference, especially in managing IT human resources and can improve the performance of the Poltekpar Lombok using IT processes EDM02 and APO08. The results of this analysis are the level of ability of IT Governance that reflects the conditions of IT governance in the Poltekpar Negeri Lombok. With improvements to the capability level provided by the COBIT 5 framework, from levels 1 to 5 at the EDM02 capability level, IT processes are at level 3.